Maximum Ride, The Manga - Book 5 5 - Lee, NaRae; Patterson, James 1947-; Lee, JuYoun (New York : Yen Press/Hachette Book Group, 2011)
Escaping ITEX in Florida, the Flock head west, with Max more burdened than ever by the knowledge that she's meant to save the world. But while their leader is keen to stay on the path leading to her destiny, Fang and the others are more interested in settling down and letting the chips fall where they may.
Keywords: Patterson, James, -- 1947- -- Adaptations; Genetic engineering -- Comic books, strips, etc; Scientists -- Comic books, strips, etc; Kidnapping -- Comic books, strips, etc; Good and evil -- Comic books, strips, etc; Genetic engineering -- Fiction; Scientists -- Fiction; Good and evil -- Fiction; Kidnapping -- Fiction; Cartoons and comics; Science fiction comic books, strips, etc; Comic books, strips, etc; Graphic novels